2013
DOI: 10.3109/00365521.2013.822092
|View full text |Cite
|
Sign up to set email alerts
|

Salvage endoscopic submucosal dissection in patients with local failure after chemoradiotherapy for esophageal squamous cell carcinoma

Abstract: ESD represents an acceptable treatment option for recurrent or residual ESCC because of its improvement in local control, when local failure after CRT is limited to the submucosal layer without metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…14,26 Moreover, it has been made available for use even in salvage ER as a feasible, effective, and safe procedure for local recurrence after definitive CRT for ESCC. 8,27,28 It is hoped that postsalvage ER pathological findings will be further elucidated with the increasing popularity of salvage ESD. Third, recurrences after salvage ER were classified in this study into locoregional recurrences and distant metastases, based on the hypothesis that risk factors for recurrence may vary between these two.…”
Section: Discussionmentioning
confidence: 99%
“…14,26 Moreover, it has been made available for use even in salvage ER as a feasible, effective, and safe procedure for local recurrence after definitive CRT for ESCC. 8,27,28 It is hoped that postsalvage ER pathological findings will be further elucidated with the increasing popularity of salvage ESD. Third, recurrences after salvage ER were classified in this study into locoregional recurrences and distant metastases, based on the hypothesis that risk factors for recurrence may vary between these two.…”
Section: Discussionmentioning
confidence: 99%
“…They used ESD to treat four patients with local recurrence of ESCC, and successfully achieved en bloc resection in all patients. Furthermore, Takeuchi et al [ 8 ] reported that ESD represents an acceptable treatment option for recurrent or residual ESCC involving only the submucosal layer without metastasis after CRT because of its effect in improving local control. They successfully treated 19 lesions in 19 patients who underwent salvage ESD.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we perform SESD in our institution. A few recent studies have reported that SESD is effective [20, 21]. They advocate consideration of SESD as a treatment option after diagnosis of esophageal superficial recurrence after dCRT for locally advanced esophageal cancer because it can achieve good local control and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including these 2, have demonstrated that R0 resection is an important prognostic factor after salvage surgery for esophageal cancer [22-25]. That is, the most important and basic consideration with salvage operation for esophageal cancer after dCRT must be complete removal of all tumor, as indicated by outcomes of SESD after dCRT for advanced cancer [20, 21]. …”
Section: Discussionmentioning
confidence: 99%